Etika Komunikasi Guru Dan Siswa Menurut Al-Zarnuji - Indah Rizkia, Indah Rizkia; Syafruddin (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2025)
Education is a process of character building that emphasises not only the transfer of knowledge, but also ethical values in the interaction between teachers and students. In the tradition of Islamic education, Al-Zarnuji's book Ta'lim al-Muta'allim is an important reference that emphasises the importance of manners and ethical communication in the teaching and learning process. This study aims to examine the concept of communication ethics between teachers and students as described by Al-Zarnuji in the book, as well as its relevance to the context of modern education. This study uses a descriptive qualitative method with a literature study approach, without involving interviews or direct observation. The main source of this study is the book Ta'lim al-Muta'allim, supported by other scientific literature. The results show that Al-Zarnuji emphasises the importance of respect, humility, patience, and sincerity in communication between teachers and students. These principles are still relevant to be applied in today's world of education, especially in shaping student character and maintaining the quality of educational relationships in the digital age.